Weight status in the 6 to 9 year-old school population in Spain: Results of the ALADINO 2015 study - Marta García-Solano; Enrique Gutiérrez-González; Ana María López-Sobaler; María Ángeles Dal Re Saavedra; Teresa Robledo de Dios; Carmen Villar-Villalba; María José Yusta-Boyo; Napoleón Pérez-Farinós (Elsevier, 2021)
Introduction: Overweight and obesity in childhood and adolescence has grown alarmingly in the last twenty years or so in many countries of Europe, including Spain. This study presents the prevalences of overweight and obesity in 6-9 year-old schoolchildren in 2015, and their associated characteristics. Methodology: ALADINO (Its initials in Spanish for Diet, physical activity, child development and obesity) is a cross-sectional study of a representative sample of 6-9 year-old schoolchildren in Spain, in line with the Childhood Obesity Surveillance Initiative (COSI) of the World Health Organisation (WHO). The height and weight of the participants, defining the weight status according to WHO standards, and a questionnaire was given to the parents on lifestyle and sociodemographic characteristics. Results: Anthropometric measurements were taken on 10,899 schoolchildren for 168 primary education centres. Excess weight was observed in 41.3% (95% CI: 40.0−42.6), overweight in 23.2% (95% CI: 22.1−24.3) and obesity in 18.1% (95% CI: 17.2−19.1), with obesity being more prevalent in boys, overweight in girls. The prevalence of abdominal obesity was 23.2% (95% CI: 21.8−24.6). The prevalence of overweight and obesity increased with age. Excess weight decreased by 3.2% compared to 2011, mainly due to the decrease in overweight in boys, while that of obesity remained stable. Excess weight was more prevalent in schoolchildren from families with a lower socioeconomic level. Conclusions: The prevalence of excess weight in 6-9 year-old schoolchildren in Spain has decreased by 3.2% since 2011, due to the decrease in overweight, whilst obesity remained stable. Action must be taken in the obesogenic environment, by promoting healthy eating habits and physical activity, bearing in mind the inequalities in health. Resumen: Introducción: El sobrepeso y la obesidad en la infancia y en la adolescencia han crecido alarmantemente en las últimas décadas en muchos países de Europa, incluido España. Este estudio presenta las prevalencias de sobrepeso y obesidad en escolares de 6 a 9 años en 2015 y sus características asociadas. Metodología: ALADINO es un estudio transversal de una muestra representativa de escolares de 6 a 9 años en España, alineado con la iniciativa COSI de la OMS. Se talló y pesó a los participantes, definiendo la situación ponderal según los estándares de la OMS, y se pasó un cuestionario a los progenitores sobre el estilo de vida y las características sociodemográficas. Resultados: Se tomaron medidas antropométricas a 10.899 escolares de 168 centros de educación primaria. El 41,3% (IC 95%: 40,0-42,6) presentaba exceso de peso, el 23,2% sobrepeso (IC 95%: 22,1-24,3) y el 18,1% obesidad (IC 95%: 17,2-19,1), siendo la obesidad más prevalente en niños y el sobrepeso en niñas. La prevalencia de obesidad abdominal era del 23,2% (IC 95%: 21,8-24,6). La prevalencia de sobrepeso y obesidad aumentaba con la edad. El exceso de peso disminuyó un 3,2% respecto a 2011, principalmente por la disminución del sobrepeso en niños, mientras que la obesidad permaneció estable. El exceso de peso era más prevalente en los escolares de familias con menor nivel socioeconómico. Conclusiones: La prevalencia de exceso de peso entre los escolares de 6 a 9 años en España ha disminuido un 3,2% desde 2011 por la disminución del sobrepeso, mientras que la obesidad permanece estable. Se debe intervenir en el entorno obesogénico, promocionando hábitos alimentarios saludables y la actividad física, incidiendo en las desigualdades en salud.